2021
DOI: 10.3390/ani11072007
|View full text |Cite
|
Sign up to set email alerts
|

Health and Welfare Survey of 30 Dairy Goat Farms in the Midwestern United States

Abstract: Dairy goat production in the Midwestern United States is increasing at a rapid rate and information on dairy goat husbandry practices applicable for producers in this region is limited. The objective of this study was to survey 30 dairy goat farms in the Midwestern US to provide insight into husbandry practices pertaining to health, welfare, and production, and to identify areas of future research. A questionnaire was developed and comprised 163 questions that were organized into categories including informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Historically, they were considered a secondary animal compared to the cow [11]. However, the demand for goat milk products such as cheese and yogurt is increasing and is likely related to changes in the demographic composition of the population, leading to an increase in the production of goat milk throughout the United States [12]. Specialized dairy livestock is concentrated in Europe and Canada.…”
Section: Resultsmentioning
confidence: 99%
“…Historically, they were considered a secondary animal compared to the cow [11]. However, the demand for goat milk products such as cheese and yogurt is increasing and is likely related to changes in the demographic composition of the population, leading to an increase in the production of goat milk throughout the United States [12]. Specialized dairy livestock is concentrated in Europe and Canada.…”
Section: Resultsmentioning
confidence: 99%
“…Technical training for staff on different husbandry practices is needed to prevent health problems and preserve animal welfare [ 67 ]. In this sense, there is a need to develop an integral welfare-monitoring program, considering animal welfare as the transversal axis in every goat husbandry practice.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…These transitions may impact health and resilience and may also be impacted by environmental conditions. A survey on the health and welfare status on 30 dairy goat farms in the USA, suggested that early kid management during birth to prevent illness/disease or mortality (e.g., warm and dry areas for kid rearing) was one of the main focus areas for future research (82).…”
Section: Safeguard Welfare Of Buck Offspringmentioning
confidence: 99%